An analytical reading of the theory of technological determinism and value determinism. -Between Marshall McLuhan and Abdel Rahman Ezzi- - GUERNANI, Yacine (Social Sciences Journal)
The theory of technological inevitability of Marshall McLuhan is one of the most important communication theories in the modern era, and that all Western and even Arab studies started from McLuhan’s ideas with the dangers that resulted from him in withdrawing their ideas and assumptions on Arab societies without taking into account the difference in cultural affiliation on the one hand, then sanctifying this theory and closing the door Diligence and theorizing of the phenomenon of communication and media in the Arab Islamic countries, and the stomachs of mothers were sterile and did not give birth to anyone looking at the phenomenon of communication in the Arab countries, but with the beginning of the eighties, new theoretical features appeared in the media in the Arab countries. Religious, intellectual and cultural heritage in the Arab-Islamic environment.